(untitled) - Totman, Conrad D. (1967)
This book provides a compelling narrative history of Japan from c. 8000 BC until the 1990s. The author examines geology, climate and agriculture; political consolidation and government; culture, literature and media; socio-economic structure and development; foreign relations, diplomacy and imperialism; industrialism and entrepreneurial growth; and social, gender and environmental issues. The book provides students and general readers with a fascinating and informative overview of the varied history of this region.
Keywords: Tokugawa family